Green tea (Camellia sinensis): Chemistry, Traditional, Medicinal uses and its Pharmacological activities- a review - Chopade, Vitthal V.; Phatak, Atul A.; Upaganlawar, Aman B.; Tankar, Anil A. (Pharmacognosy Reviews)
The Green tea is obtained from the tea plant Camellia sinensis (L.) Kuntze (Common names: Green tea extract, Chinese tea) which belongs to the family Theaceae. Itis a widely used medicinal plant by the tribals throughout India, China and popular in various indigenous system of medicine like Ayurveda, Unani and Homoeopathy Green tea has been consumed throughout the ages in India, China, Japan, and Thailand. Following the various traditional claims on utility of this plant in curing number of diseases, considerable efforts have been made by researchers to varify its utility through scientific pharmacological screenings. In traditional Chinese and Indian medicine, practitioners used green tea as a stimulant, diuretic (to promote the excretion of urine), astringent (to control bleeding and help heal wounds), and to improve heart health. Other traditional uses of green tea include treating flatulence (gas), regulating body temperature and blood sugar, promoting digestion, and improving mental processes.
Keywords: Green tea; Camellia sinensis; Chemistry; Traditional and harmacological activities